2015
DOI: 10.1332/204674315x14381836678553
|View full text |Cite
|
Sign up to set email alerts
|

Researching surviving cancer and sexuality using visual methods: a reflection on research rationale and negotiating ethical issues

Abstract: This article offers an account of incorporating visual methods into a research framework inspired by graphic medicine, where comics are used in patient care. We conducted interviews, focused on sexual wellbeing, with 12 leukaemia survivors. The findings from these interviews were transformed into visual representations. We outline how our study was guided by feminist research principles and reflect on the tension between the flexibility that visual methods require and the rigidity of National Health Service et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…This is consistent with results from a systematic review of the role of pictures in improving communication, which showed that the use of drawings, especially when they are closely linked to related verbal messages, is associated with higher attention to and recall of health education materials, compared with text alone [ 14 ]. Drawings have also proved to be an effective tool for facilitating critical reflection and dialogue around sensitive health issues [ 15 ], for instance, sexual dysfunction in cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with results from a systematic review of the role of pictures in improving communication, which showed that the use of drawings, especially when they are closely linked to related verbal messages, is associated with higher attention to and recall of health education materials, compared with text alone [ 14 ]. Drawings have also proved to be an effective tool for facilitating critical reflection and dialogue around sensitive health issues [ 15 ], for instance, sexual dysfunction in cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%